A comprehensive provincial-level VOCs emission inventory and scenario analysis for China: Enhanced sectoral resolution through GAINS-China model - Zhao, Yuhang; Sun, Hong; Kim, Younha; Shu, Yun; Wang, Han; Li, Hui; Deng, Yinhe (Atmospheric Environment: X, 2025)
Volatile organic compounds (VOCs) are key precursors to secondary organic aerosol (SOA) and ground-level ozone, posing significant challenges to air quality and public health in China. Although previous studies have established VOCs inventories and projected emission trends, many lack the granularity needed to capture sectoral and regional emission variations, especially within the highly contributive solvent use sector. To address this gap, this study aims to develop a detailed VOCs emission inventory for China at the provincial level for 2020, utilizing the GAINS-China model and covering 5 major sectors, 20 subsectors, and 80 distinct emission sources. Uniquely, this inventory subdivides the solvent use sector into 5 subsectors and 22 specific sources, enabling a more precise analysis of VOCs emission sources. Future emission trends and reduction potentials were projected for the period 2020–2050 under two scenarios: reference (REF) and current legislation (CLE). The results revealed that the total anthropogenic VOCs emissions in China were estimated to be 23,114.8 kt in 2020, with solvent use contributing 56.0%, followed by the residential (17.0%), others (11.0%), transportation (10.0%), and industry and power (6.0%) sectors. Under the REF scenario, VOCs emissions are expected to decline to 19,162.2 kt by 2040 but remain stable thereafter. This reduction is driven mainly by the replacement of household solid fuels with clean fuels in the residential sector, especially in Sichuan Province. Compared with those in the REF scenario, the total VOCs emissions in the CLE scenario continuously decreased throughout 2020–2050, with the solvent use sector contributing the most to the reductions (46.1%–81.7%), followed by transport (16.8%–41.3%). A provincial analysis highlights that high-emission regions such as Guangdong, Jiangsu, and Shandong offer the greatest reduction potential. To effectively and precisely reduce VOCs emissions, key subsectors contributing to emissions, including paint use, non-road machinery, industrial processes, and agriculture, should be prioritized for further control measures. This study provides essential insights into sectoral and regional VOCs emissions, offering a robust foundation for formulating targeted emission control policies. •Developed a provincial-level VOCs emission inventory covering 5 sectors and 80 sources.•Subdivided the solvent use sector into 5 subsectors and 22 specific sources.•Identified key VOCs reduction priorities in high-emission regions and subsectors.